Effects of molecular diffusion length on area-selective growth of organic patterns. (1st March 2022) - Jiang, Yue; Cai, Yichen; Li, Jianping; Chen, Naibo; Hu, Laigui; Wang, Wenchong; Nie, Qing-Miao; Yan, Bo
Abstract: Oganic devices have gained much progress in the past decades, as a promising candidate for flexible/wearable electronics. However, the realization of organic microelectronic systems for wide applications is still difficult, due to the incompatibility of organic semiconductors (OSCs) with the conventional top-down lithography techniques for inorganics. To solve this challenge, bottom-up lithography-compatible methods have been developed for organic device arrays, i.e., template-directed growth or area-selective growth (ASG). Unfortunately, the physics on the dynamic process of the ASG method for molecular semiconductors is still not well understood. In order to explore this issue, the growth of particles on prepatterned surfaces under different diffusion lengths ( L d ) was simulated in a microscopic point of view by using kinetic Monte Carlo method. Simulation results show that ASG of the particles is strongly related to the L d of the particles, periodicity and size of prepatterned surfaces. It is notable that such simulated results were found to fit well with those of our experiments, which can be favorable for improving the ASG method for patterning functional molecules.